LINC00174 is an oncogenic lncRNA of hepatocellular carcinoma and regulates miR‐320/S100A10 axis - Zhao, Jin‐Tao; Chi, Bao‐Jin; Sun, Yao; Chi, Nan‐nan; Zhang, Xue‐mei; Sun, Jia‐bin; Chen, Ying; Xia, Yong (Cell biochemistry and function, 2020)
Hepatocellular carcinoma (HCC) is one of the deadliest cancers. Multiple long non‐coding RNAs (lncRNAs) are recently identified as crucial oncogenic factors or tumour suppressors. In this study, we explored the effects of LINC00174 on the progression of HCC. Expression levels of LINC00174 and microRNA‐320 (miR‐320) in HCC tissue samples were measured using quantitative real‐time polymerase chain reaction (qRT‐PCR). The association between pathological indices and LINC00174 was also analysed. Human HCC cell lines Hep3B and Huh7 were used as cell models. CCK‐8 and bromodeoxyuridine (BrdU) assays were used to assess the effect of LINC00174 on HCC cell line proliferation. Flow cytometry was used to study the effect of LINC00174 on HCC apoptosis. Transwell assay was conducted to detect the effect of LINC00174 on migration and invasion. Furthermore, luciferase reporter assay and RNA immunoprecipitation (RIP) assay were used to confirm the binding relationship between miR‐320 and LINC00174. Additionally, western blot was used to detect the regulatory function of LINC00174 on oncogene S100 calcium binding protein A10 (S100A10). We demonstrated that LINC00174 expression in HCC clinical samples was significantly increased and this was correlated with higher T stage. Its overexpression remarkably accelerated proliferation and metastasis of HCC cells while reduced apoptosis. Accordingly, knockdown of it suppressed the malignant phenotypes of HCC cells. Overexpression of LINC00174 significantly reduced the expression of miR‐320 by sponging it, in turn enhanced the expression of S100A10. In conclusion, LINC00174 is a sponge of tumour suppressor miR‐320, enhances the expression of S100A10 indirectly and functions as an oncogenic lncRNA in HCC. Significance of the study LINC00174 is a novel lncRNA, whose function is rarely investigated. It is reported that it is oncogenic in colorectal cancer, while its role in HCC remains unclear. Herein, we report that LINC00174 is significantly up‐regulated in HCC tissues and promotes the malignant phenotypes. We demonstrate that LINC00174 functions as a sponge for miR‐320, increases the expression level of oncogene S100A10 in HCC. This study helps clarify the mechanism of HCC tumorigenesis and progression, and uncover the role of LINC00174 in human disease.